Endoscopic approach for diagnosing autoimmune pancreatitis - Kamisawa, Terumi (Baishideng Publishing Group Co., Limited, 2010)
It is of utmost importance to differentiate autoimmune pancreatitis (AIP) from pancreatic cancer (PC). Segmental AIP cases are sometimes difficult to differentiate from PC. On endoscopic retrograde cholangiopancreatography, long or skipped irregular narrowing of the main pancreatic duct (MPD), less upstream dilatation of the distal MPD, side branches derived from the narrowed portion of the MPD, absence of obstruction of the MPD, and stenosis of the intrahepatic bile duct suggest AIP rather than PC. Abundant infiltration of IgG4-positive plasma cells is frequently and rather specifically detected in the major duodenal papilla of AIP patients. IgG4-immunostaining of biopsy specimens obtained from the major duodenal papilla is useful for supporting a diagnosis of AIP with pancreatic head involvement. On endoscopic ultrasonography (EUS), hyperechoic spots in the hypoechoic mass and the duct-penetrating sign suggest AIP rather than PC. EUS and intraductal ultrasonography sometimes show wall thickening of the common bile duct even in the segment in which abnormalities are not clearly observed with cholangiography in AIP patients. EUS-guided fine needle aspiration, especially EUS-guided Tru-Cut biopsy, is useful to diagnose AIP, as well as to exclude PC.